2019
DOI: 10.1111/jcmm.14491
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling identifies PDLIM2 as a novel prognostic predictor for oesophageal squamous cell carcinoma (ESCC)

Abstract: Till now, no appropriate biomarkers for high‐risk population screening and prognosis prediction have been identified for patients with oesophageal squamous cell carcinoma (ESCC). In this study, by the combined use of data from the Gene Expression Omnibus (GEO) datasets and The Cancer Genome Atlas (TCGA)‐oesophageal carcinoma (ESCA), we aimed to screen dysregulated genes with prognostic value in ESCC and the genetic and epigenetic alterations underlying the dysregulation. About 222 genes that had at least fourf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Recent studies constructed prognostic models for ESCC based on gene expression data, with the aim of improving its early diagnosis and personalized treatment. Song et al integrated the analysis of ESCC microarray data from GDS3838 and TCGA-ESCC and confirmed the prognostic value of PDLIM2 expression, which was independently associated with longer OS in ESCC patients [28]. In the current study, the risk score tends to be larger with lower expression of PDLIM2, and ESCC patients with a high-risk score had significantly poorer OS.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies constructed prognostic models for ESCC based on gene expression data, with the aim of improving its early diagnosis and personalized treatment. Song et al integrated the analysis of ESCC microarray data from GDS3838 and TCGA-ESCC and confirmed the prognostic value of PDLIM2 expression, which was independently associated with longer OS in ESCC patients [28]. In the current study, the risk score tends to be larger with lower expression of PDLIM2, and ESCC patients with a high-risk score had significantly poorer OS.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to sex chromosome-encoded genes, several autosomal genes were up-regulated in adenomas from male patients; of note, PDLIM2, PENK, SOX4, FH, PTMA and TMEM97 are all associated with tumourigenesis [64][65][66][67][68][69], and thus could play a role in the less favourable course of corticotrope adenomas in male patients. Links between these factors and the pituitary are known for PTMA and SOX4, as PTMA nuclear staining has been linked to pituitary tumour size [70], and SOX4 is involved in pituitary development, as shown in both zebrafish [71] and human tissues [72].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, these two databases are widely used for data mining due to their large sample size and complete clinical information. Many studies have identified various biomarkers for ESCC based on TCGA and GEO databases [3][4][5][6][7][8][9]. For example, Mao et al identified a seven-lncRNA signature to predict overall survival in ESCC, which displayed better prognostic predict ability than tumor-node-metastasis (TNM) stage.…”
Section: Ivyspring International Publishermentioning
confidence: 99%